Rates of interventional procedures in patients with tuberous sclerosis complex-related renal angiomyolipoma. (3rd August 2015) - Bissler, John; Cappell, Katherine; Charles, Hearns; Song, Xue; Liu, Zhimei; Prestifilippo, Judith; Hulbert, John
Abstract: Objective: To describe rates of renal artery embolization, partial nephrectomy, and complete nephrectomy in patients with tuberous sclerosis complex (TSC) and renal angiomyolipoma. Methods: Data from the MarketScan® Research Databases were used to select patients with TSC and renal angiomyolipoma during January 1, 2000–March 31, 2013 (Commercial database) and January 1, 2000–June 30, 2012 (Medicaid database). Patients had at least 30 days of follow-up and were followed until the earliest of inpatient death, end of enrollment, or end of study. Rates of embolization and nephrectomy were calculated. Results: In total, 218 patients <18 years (mean = 9.7 years) and 378 patients ≥18 years (mean 36.9 years) were selected from the Commercial database. Fifty-nine patients <18 years (mean = 7.2 years) and 117 patients ≥18 years (mean = 37.2 years) were selected from the Medicaid database. Follow-up in the Medicaid cohorts was approximately twice that of the Commercial cohorts. Among patients in the study, 24.2% had at least one interventional procedure: 15.2% had embolization, 5.2% had partial nephrectomy, and 7.6% had complete nephrectomy. Within the Commercial cohort ≥18 years, 18.5% had embolization, 7.7% had partial nephrectomy, and 11.4% had complete nephrectomy. Corresponding percentages in the Medicaid adult cohort were 17.1%, 5.1%, and 4.3%. Repeat embolization procedures occurred in up to 7.7% of Commercial patients and in up to 6.8% of Medicaid patients. Repeat partial nephrectomy occurred in up to 4.5% and 1.7% of Commercial and Medicaid patients, respectively. Conclusions: Approximately 25% of patients with TSC-renal angiomyolipoma experienced embolization or nephrectomy, with some patients undergoing repeat procedures. Study limitations included small sample sizes, the majority of the study period occurred prior to the approval of mammalian target of rapamycin inhibitors for the treatment of TSC-renal AML, and results may not be generalizable to patients with insurance other than commercial or Medicaid.